Aplicação do regulamento técnico da qualidade para etiquetagem do nível de eficiência energética de edifícios: o caso do Centro de Tecnologia da UFSM - Klüsener, Cibele Sangoi (2009)
The Technical Regulation for Labeling Quality Level of Energy Efficiency of Buildings aims to specify the technical requirements and methods for the classification of commercial buildings, and public services on energy efficiency. This paper evaluate the applicability of the Regulation from the point of view of architectural practice and examine the influence of variables that determine the classification of the building of the Center for Technology, Federal University of Santa Maria - RS. A partial classification as the three main requirements set by regulations, Envelopment, Lighting System and Air-conditioning System and the general classification of the level of efficiency of the building were determined by the pre-service requirements, general and specific, and the application of the method prescriptive. The creation of hypothetical scenarios has highlighted the influence of variables that determine the level of energy efficiency building. The relevance of the methodology for its incorporation as a tool to highlight that the project supports implementation of the Regulation can contribute to energy efficient solutions, and encourage the construction and evaluation of buildings that have high levels of efficiency or progressive.